2021
DOI: 10.1016/j.csbj.2021.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Making fundamental scientific discoveries by combining information from literature, databases, and computational tools – An example

Abstract: In recent years, the amount of available literature, data and computational tools has increased exponentially, providing opportunities and challenges to make use of this vast amount of material. Here, we describe how we utilized publicly available information to identify the previously hardly characterized protein SAMD1 (SAM domain-containing protein 1) as a novel unmethylated CpG island-binding protein. This discovery is an example, how the richness of material and tools on the internet can be used to make sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Consequently, the absence of SAMD1 typically leads to the derepression of its target genes 4 , 9 . SAMD1 is often upregulated in cancer tissues and correlates with worse prognosis in some cancer types, such as adenoid cystic carcinoma (ACC) and liver cancer 9 , 13 . A CRISPR screen in K562 cells suggested that SAMD1 is required for the efficient proliferation of these cells 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the absence of SAMD1 typically leads to the derepression of its target genes 4 , 9 . SAMD1 is often upregulated in cancer tissues and correlates with worse prognosis in some cancer types, such as adenoid cystic carcinoma (ACC) and liver cancer 9 , 13 . A CRISPR screen in K562 cells suggested that SAMD1 is required for the efficient proliferation of these cells 14 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, KDM2B and mammalian Polycomb-like proteins are associated with Polycomb repressive complexes and are involved in gene repression ( 33–35 ). Recently, we identified the SAM domain-containing protein 1 (SAMD1) as another protein that specifically binds to unmethylated CpG motifs ( 36 , 37 ). SAMD1 is associated with L3MBTL3 and the KDM1A histone demethylase complex and functions as a transcriptional repressor ( 36 , 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…SAMD1 has homology across primates, canines, rodents, and rabbits, and orthology with at least 250 organisms, and SAMD1 RNA is found in numerous organs and tissues in humans and mice [1], [2], [3]; the extensiveness of expression suggests roles in adult homeostasis. SAMD1 was minimally studied until very recently [4]. A 2021 report supports SAMD1's participation in LDL retention and uptake, finding that SAMD1 knockdown suppresses Vascular Smooth Muscle Cell (VSMC) differentiation and proliferation, and that SAMD1/LDL binding on VSMCs leads to LDL oxidation and foam cell development [5].…”
Section: Introductionmentioning
confidence: 99%